WORLD DIABETES DAY 2023 (Baqai Journal of Health Sciences)
On November 19, 2023, the Diabetes Association of Pakistan (DAP) orchestrated a significant event in Karachi, marking World Diabetes Day (WDD) 2023. Held at a local hotel, the event commenced with an inaugural address by Abdul Basit and MianMukhtar Ahmed. The scientific program overseen by the Chairperson Prof. Dr. ShabeenNazMasoodforWDD-DAP.She said she is delighted to welcome in the DiabetesAssociation of Pakistan (DAP) Scientific Session, a platform dedicated to advancing our understanding of diabetes prevention and advocacy. This session is